Hyperthyroidism with dome-and-dart T wave: A case report: A care-compliant article. Issue 6 (February 2017) - Lai, Ping; Yuan, Jing-ling; Xue, Jin-hua; Qiu, Yue-qun
Abstract: Rationale: Dome-and-dart T waves (or bifid T waves) are a rare phenomenon in the surface electrocardiogram. These wave forms are mainly observed in patients with congenital heart disease such as atrial septal defect and ventricular septal defect. And hyperthyroidism who presented with an electrocardiogram that had dome-and-dart T waves in a precordial lead is never been reported. Patient concerns: The patient presented with continuous tachycardia, palpitations, chest tightness, and headache for 4 days, and aggravated for 1 day. Diagnoses: Hyperthyroidism. Interventions: Methimazole. Outcomes: All symptoms were alleviated. Lessons: Dome-and-dart or bifid T waves have been reported in the conventional 12-lead electrocardiograms in some patients with congenital heart disease. The case illustrated here, to the best of our knowledge, dome-and-dart or bifid T waves may associate with hyperthyroidism patients.